Precarity to empowerment: the consequences of female North Korean defectors' coping skills and social navigation. Issue 11 (1st November 2022) - Shin, HaeRan
Abstract: This ethnographic study of female North Korean defectors in the UK opens discussions on the notion that agency and social navigation can countermand economic and political precarity to the point of empowerment. I challenge existing literature and schools of thought that precarity is double edged and suggest the term of social navigation, which these women employ to traverse their shifting environment leading to unintentional empowerment. By documenting North Korean women's plight from the 1994 to 1998 famine in North Korea to their defection to South Korea and subsequent resettlement to London's New Malden, I plot their progression and growing confidence as they parlay precarity to empowerment. Research collected on their lives during the economic crisis in North Korea before defection revealed their resourceful and somewhat defiant ventures into capitalist-style markets. Analysing the results of the fieldwork conducted in a suburb of New Malden's Koreatown, I discovered that these women's adaptability and ethnic networks enabled them to not only survive uncertain situations but thrive. The shift from care-giver to bread-winner that started in North Korea was consolidated in the UK as they once again turned adversity to an advantage when the UK government decreased financial support. In the Korean community, by focusing on educational and cultural activities instead of political turmoil, those women have been able to focus on moving forward. As a result, they have found a power in themselves to make differences in their lives.